Antibacterial Effect of Sodium Hypochlorite and EDTA in Combination with High-Purity Nisin on an Endodontic-like Biofilm Model - Ericka T. Pinheiro; Lamprini Karygianni; Thomas Attin; Thomas Thurnheer (MDPI AG, 2021)
Antimicrobial peptides have been proposed as antibiofilm agents. Therefore, we evaluated the effect of endodontic irrigants combined or not with the antimicrobial peptide nisin against an endodontic biofilm model composed of eleven bacterial species. Biofilms were grown on hydroxyapatite discs for 3, 15 and 21 days and treated with 1.5% sodium hypochlorite (NaOCl) or 17% EDTA followed by high-purity nisin (nisin ZP) or saline for 5 min each. Differences between groups were tested by two-way ANOVA and Tukey's multiple comparisons test (p < 0.05). Treatment with 1.5% NaOCl completely eliminated 3-d and 15-d biofilms but did not eradicate 21-d biofilms. Treatment with 1.5% NaOCl and 17% EDTA was equally effective against 21-d biofilms, showing 5-log and 4-log cell reduction, respectively, compared to the untreated control (9 log10, p < 0.05). No significant difference was found between 1.5% NaOCl + nisin ZP and 1.5% NaOCl in 21-d biofilms (p > 0.05). Likewise, no significant difference was found between 17% EDTA + nisin ZP and 17% EDTA treatments (p > 0.05). In conclusion, 1.5% NaOCl or 17% EDTA were effective strategies to combat mature biofilms. The additional use of nisin did not improve the activity of conventional irrigants against multispecies biofilms.